Advocacy Corner: The Case for Ohio’s Mathematical Modeling and Reasoning Course - Miller, Steve; Walls, Jennifer L (Ohio Journal of School Mathematics, 2021)
In the following policy brief, the authorsdiscuss recent steps by the Ohio Mathematics Initiative to better align mathematics coursework to the college and career goals of Ohio’s students. They argue for a Modeling and Reasoning course to better meet the needs of various majors and careers and to help ensure student success in college-level mathematics courses.